Magnesium versus titanium headless compression screws for fixation of a Hoffa-type fracture - a biomechanical in-vitro study - Larissa Felten; Filippo Migliorini; Frank Hildebrand; Christian David Weber (BMC Musculoskeletal Disorders)
Abstract Background Intraarticular (e.g., Hoffa-type) fractures are usually stabilized with titanium screws, which may necessitate later implant removal. The aim of this study was to compare the biomechanical strength and stability of magnesium and titanium screws. Methods 18 double-layer bone blocks were fixed with 18 one-layer bone blocks and divided into 2 groups based on the fixation method: magnesium screw fixation (Magnesium group, n = 9) and traditional titanium screw (Titanium group, n = 9). Compressive force was applied to the specimens orthogonally to the screw axis. First, axial stiffness was measured, and a cyclic loading test was performed, after 10, 100, 1000 and 10,000 cycles respectively, and the axial displacements were recorded. Finally, the specimens were loaded to failure. Results There were significant differences between the groups with respect to axial stiffness and cyclic loading. The ultimate failure load was comparable. The average axial stiffness for the magnesium group was 326 ± 67 N/mm and for the titanium group 266 ± 72 N/mm (p = 0.031). The axial displacement relative to 100 N preload after 10,000 cycles in the magnesium group was 1.7319 ± 0.2261 mm and in the titanium group 2.6932 ± 0.5921 mm (p < 0.001). The average ultimate failure in the magnesium group was 920 ± 55 N and in the titanium group 944 ± 40 N (p = 0.293). Conclusions Based on the results magnesium screws show at least a comparable strength and stability as titanium screws in this setting. This study provides support from a biomechanical perspective for the use of magnesium screws in Hoffa fractures. Clinical trial number Not applicable.